Comprehensive characterization of the peroxisome proliferator activated receptor‐δ agonist GW501516 for horse doping control analysis. Issue 6 (11th February 2021) - Trevisiol, Stéphane; Moulard, Yves; Delcourt, Vivian; Jaubert, Murielle; Boyer, Sophie; Tendon, Sophie; Haryouli, Hayate; Taleb, Wafek; Caroff, Mylène; Chabot, Benjamin; Drif, Laura; André, François; et al.
Abstract: According to international sport institutions, the use of peroxisome proliferator activated receptor (PPAR)‐δ agonists is forbidden at any time in athlete career due to their capabilities to increase physical and endurance performances. The (PPAR)‐δ agonist GW501516 is prohibited for sale but is easily available on internet and can be used by cheaters. In the context of doping control, urine is the preferred matrix because of the non‐invasive nature of sampling and providing broader exposure detection times to forbidden molecules but often not detected under its native form due to the organism's metabolism. Even if urinary metabolism of G501516 has been extensively studied in human subjects, knowledge on GW501516 metabolism in horses remains limited. To fight against doping practices in horses' races, GW501516 metabolism has to be studied in horse urine to identify and characterize the most relevant target metabolites to ensure an efficient doping control. In this article, in vitro and in vivo experiments have been conducted using horse S9 liver microsome fractions and horse oral administration route, respectively. These investigations determined that the detection of GW501516 must be performed in urine on its metabolites because the parent molecule was extremely metabolized. To maximize analytical method sensitivity, the extraction conditions have been optimized. In accordance with these results, a qualitative analytical method was validated to detect the abuse of GW501516 based on its most relevant metabolites in urine. This work enabled the Laboratoire des Courses Hippiques (LCH) to highlight two cases of illicit administration of this forbidden molecule in post‐race samples. Abstract : The study of GW501516 metabolism in horse determined that the detection of its misused must be performed in urine on its metabolites because the parent molecule was extremely metabolized.